2004
DOI: 10.1111/j.0736-8046.2004.21215.x
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Bullous Pemphigoid: Report of a Case with Life‐Threatening Course During Homeopathy Treatment

Abstract: Bullous pemphigoid (BP) is an autoimmune blistering disorder that may very rarely occur in childhood. We describe a 9-month-old child who developed bullous pemphigoid while she was being treated for presumptive atopic eczema with a homeopathic regimen comprising sulfur, mercury, cantharides, and Rhus (Toxicodendron). She had generalized bullae and a progressive worsening of her general condition with asthenia, dehydration, malnutrition. While the role of homeopathy in triggering the disease remains unclear, ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 30 publications
3
32
0
Order By: Relevance
“…It is important with regard to patient safety that homeopaths do not ignore signs of serious adverse effects (red flag situations) and thus provoke a dangerous situation for the patients. Consequences of overlooking serious symptoms are demonstrated in the case presented previously [4] and in a systematic review recently published [28]. …”
Section: Risk Assessment and Patient Safetymentioning
confidence: 91%
See 2 more Smart Citations
“…It is important with regard to patient safety that homeopaths do not ignore signs of serious adverse effects (red flag situations) and thus provoke a dangerous situation for the patients. Consequences of overlooking serious symptoms are demonstrated in the case presented previously [4] and in a systematic review recently published [28]. …”
Section: Risk Assessment and Patient Safetymentioning
confidence: 91%
“…Data from observational studies and surveys [24] reveal that reported adverse effects from homeopathic treatment fluctuate between 2 and 11% [25]. Several cases published in scientific literature confirm these findings [4,26,27]. A review of case reports published in 2012 [28] reported that among the 38 primary cases included, 30 pertained to direct adverse effects of homeopathic remedies of different potencies and another 8 were related to adverse effects caused by substituting homeopathy for conventional medicine.…”
Section: Risk Assessment and Patient Safetymentioning
confidence: 97%
See 1 more Smart Citation
“…We are not aware of a high prevalence of atopy in BP patients, although there is a report of BP in an atopic girl on homeopathic therapy [13] . In our patient, the persistently elevated IgE levels that had already been detected 23 years before the appearance of BP are probably more related to atopy than to BP.…”
Section: Introductionmentioning
confidence: 90%
“…In one case (28), a nine-month old baby girl was given several homeopathic remedies to treat atopic dermatitis. The child developed Bullous Pemphigoid (BP) during the treatment period and when the baby was finally admitted to the hospital, the condition was life threatening.…”
Section: Introductionmentioning
confidence: 99%